Fundamental of Entrepreneurship (ENT300) : SK Hardware (Kuching) Sdn Bhd retail hardware store business/ Ariesha Aki … [et al.] - Aki, Ariesha; Terry, Jessylyn Jelenny; Ayung Bangga, Mary Michelle (2017)
Being one of the retail hardware stores in Malaysia, SK Hardware aims to gives new experience to the customers who shop at their shop. It is located at Miles 5, Jalan Penrissen, 93250, Kuching, Sarawak. This is the second main branch ofthis company other than their mini branch which is SK Lifestyles and SK Comer. SK Hardware is a family business/company that was owned by the Law’s family. Over the years, SK Hardware has provided variety choices of household appliances namely paint, vacuum, screw, pipes, and many more. They also held consultation with their customers in their choice of paint color design.